AIR BUBBLE PANEL FOR INFORMATION PROTECTION FROM LEAKAGE VIA TECHNICAL CHANNELS - O. B. Zelmanski; S. N. Petrov; A. A. Kazeka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The description of the design and characteristics of the low weight and size combined air bubble panel for information protection from a leakage via acoustic, electromagnetic and optical technical channels are considered. Values of speech intelligibility of speech signal passed through the developed construction and electromagnetic radiation shielding properties of the panel are discussed.